Bankruptcy Prediction of Boycotted Firms Using Altman Z-Score Analysis: Prediksi Kebangkrutan Perusahaan yang Diboykoti Menggunakan Analisis Altman Z-Score - Rosfian, Ilma Zulfiana; Hanun, Nur Ravita (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Consumer boycotts linked to the Israel–Palestine conflict have created financial pressure on several Indonesian companies, prompting the need to assess their financial resilience. Specific Background: Despite widespread public action, limited studies investigate how boycotts influence bankruptcy risk using financial ratio models. Gap: Previous research applies Altman Z-Score in various sectors, yet none focuses on boycott-affected firms within a social–political context. Aim: This study analyzes bankruptcy prediction among Indonesia Stock Exchange companies allegedly affected by consumer boycotts during 2019–2023 using the Altman Z-Score model. Results: Findings show heterogeneous financial conditions: food and beverage companies such as FAST, MAPB, and PZZA experienced declining Z-Scores indicating distress, while ADES, ULTJ, and MTDL maintained strong financial stability. All four ratios (WCTA, RETA, EBITTA, MVEBVL) exhibit significant positive contributions to Z-Score, confirming their relevance in predicting financial resilience. Novelty: This research integrates Altman Z-Score with signaling and agency theory to explain how managerial decisions and market perceptions shape corporate stability during boycott pressures. Implications: The results provide practical insights for investors, managers, and policymakers in evaluating risk exposure and developing strategies to strengthen corporate resilience under socio-political disruptions. Highlights:• Companies show varied financial resilience under consumer boycott• Altman Z-Score identifies vulnerable and stable firms accurately• Working capital, retained earnings, EBIT, and equity strength drive stability Keywords: Altman Z-Score, Bankruptcy Prediction, Consumer Boycott, Financial Ratios, Indonesia Stock Exchange